2016
DOI: 10.21037/jtd.2016.06.04
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of cytoreductive surgery combined with intrapleural perfusion of hyperthermic chemotherapy in advanced lung adenocarcinoma with pleural dissemination

Abstract: Background: This study aimed to investigate the safety and feasibility of intrapleural perfusion hyperthermic chemotherapy (IPHC) followed by cytoreductive surgery as a part of multimodal strategy for the treatment of advanced lung adenocarcinoma. Methods: Medical records of advanced lung cancer patients with pleural dissemination who underwent surgical treatment between 2003 and 2013 were reviewed retrospectively. Enrolled patients were divided into a surgery group comprising patients who underwent surgery on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…This modality also can be applied in lung cancer with pleural dissemination, as reported by Yi and colleagues. 53 The investigators used a 90-minute perfusion of 150 mg/m 2 of cisplatin with mannitol and thiosulphate protection at 43 to 45°C. There was statistically significant improvement of overall survival at 6 months, 1 year, and 3 years (95.7%, 91.3%, and 38.6% vs 80.0%, 80.0%, and 37.5%) and trend toward improved progression-free survival (87.0%, 47.8%, and 24.3%, vs 44.4%, 33.3%, and 0.0%).…”
Section: Resultsmentioning
confidence: 99%
“…This modality also can be applied in lung cancer with pleural dissemination, as reported by Yi and colleagues. 53 The investigators used a 90-minute perfusion of 150 mg/m 2 of cisplatin with mannitol and thiosulphate protection at 43 to 45°C. There was statistically significant improvement of overall survival at 6 months, 1 year, and 3 years (95.7%, 91.3%, and 38.6% vs 80.0%, 80.0%, and 37.5%) and trend toward improved progression-free survival (87.0%, 47.8%, and 24.3%, vs 44.4%, 33.3%, and 0.0%).…”
Section: Resultsmentioning
confidence: 99%
“…HU et al [22] performed video-assisted thoracoscopic surgery pleural biopsy and HITHOC in 54 patients with malignant pleural effusion caused by lung carcinoma with a median survival of 21.7 months and a 1-year survival rate of 74.1%. YI et al [23] performed an interesting study on 23 patients with advanced lung adenocarcinoma who underwent debulking surgery alone versus debulking surgery with HITHOC, which was continued for only 30 min (compared with 60 min in our technique). The complication rate was 34.8% versus 40%, while the 3-year survival rate was 24.3% versus 0% ( p=0.045), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The standard care of patients with NSCLC is chemoradiotherapy for stage III and chemotherapy for stage IV. Previous studies have reported that cytoreductive surgery can improve the quality of life of patients with advanced or distant metastasis of lung cancer (25,26); hence, the 29 NSCLC patients diagnosed with stage III-IV admitted in our study received cytoreductive surgery. NSCLC tissues and adjacent normal tissues were obtained after surgical resection and immediately frozen and conserved in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%